Імпортозаміщення ліфтового обладнання у публічних закупівлях: проблеми та напрями стимулювання - Snigova, Olena Yu. (Institute of Industrial Economics of NAS of Ukraine, 2024)
The problem of import substitution is relevant for any country, taken into account the requirements of its economic self-sufficiency, independence on the situation at the international markets and on geopolitical changes. For Ukraine in the state of full-scale war, this task is important from the viewpoints of economic resilience and security. For this reason, the Government determined the substitution of import components in public procurements as one of the priorities of its activity. Solving this problem will be important for the projects associated with the procurement for the recovery of infrastructure in post-war period.The sector of elevator equipment production has a significant industrial potential for the post-war recovery of infrastructure in Ukraine. Extension of industrial capacity of this segment of machine building in order to cover the domestic market requirements in post-war recovery period will enable new job creation and will provide a multiplicative effect based on the development of complementary suppliers of production components. However, a number of problems prevents Ukrainian elevator equipment producers from winning in public procurements.The goal of the article is to substantiate the reasonability and to determine the directions and stimulating measures for elevator equipment import substitution in public procurements in Ukraine.The market of elevator equipment of Ukraine has been analyzed. The capacity of Ukrainian elevator equipment producers to compete at the domestic market has been assessed based on price, warranty terms, cost of warranty service, and quality of equipment.Public procurement of elevator equipment and maintenance services in “Prozorro” system has been studied. It was found that about 70 % of public procurements of elevator equipment account for the purchases of imported equipment from Turkey and China. The problems of domestic producers of elevator equipment preventing them from winning the public procurement have been explained.The multiplicative effect from the increase of public procurements of elevator equipment from national producers has been assessed. This proves the reasonability to stimulate import substitution of elevator equipment in public procurements. The directions and measures of elevator equipment import substitution stimulation in public procurements in Ukraine have been suggested.